Thiol-Ene Coupling Reaction for Functionalization of Non-Activated Alkenes: An Experimental Study on the Chemistry of the Methyl Oleate Amination - Polo, Mara Lis (2024)
This work investigates the functionalization of molecules with non-activated internal double bonds via thiol-ene coupling (TEC) reaction. A comprehensive study of the reaction between cysteamine hydrochloride (CAHC) and methyl oleate (MO) was carried out. A series of reactions were conducted under different operating conditions in order to assess their effect on conversion and selectivity. Different conditions were considered like the type of atmospheres and solvents, a portionwise addition of CAHC, reagents concentrations, and excess of CAHC. Maximum conversion and selectivity were reached under inert atmosphere, diluted conditions, ethanol as solvent, and the addition of CAHC at the beginning of the reaction with a molar ratio of CAHC/MO of 3/1. This provides an approach for analyzing more complex reaction systems